Estudio de la situación socio-lingüística de la vitalidad de kichwa. Análisis de caso en la comunidad Atapo Quichalán, provincia de Chimborazo - Roldán Roldán, Virgilio (2017)
The main objective is to determine how vital Kichwa is to indigenous communities and to discover the attitude native speakers have towards the language. Furthermore, the investigation clarifies the role of Kichwa in the construction of the native speakers' identities. This work was completed through investigations in the field and bibliographic research. Additionally, information was gathered through observations, interviews, review of legal norms, books, and websites. The majority of the population that participated considers the language to be very important to the identity of indigenous towns and to be a thousand-year-old treasure that survives today in social, cultural, and educational aspects of the community. Faced with this reality, the community aspires to value the language in a more permanent way, revitalizing the language among young people who present negative attitudes toward their own culture and language due to thoughts introduced by the globalized world and the colonization which often confuses and minimizes our identity. Based on the results of the investigation after processing the data, it is clear that the Kichwa language is highly valued by the inhabitants of the community. This signifies that the native language continues to thrive at an oral level and in informal situations. However, it is necessary to strengthen the language through various approaches in order to keep Kichwa alive in written works and formal situations.